2009
DOI: 10.3758/app.71.4.724
|View full text |Cite
|
Sign up to set email alerts
|

Motion fading and the motion aftereffect share a common process of neural adaptation

Abstract: After prolonged viewing of a slowly drifting or rotating pattern under strict fixation, the pattern appears to slow down and then momentarily stop. Here, we show that this motion fading occurs not only for slowly moving stimuli, but also for stimuli moving at high speed; after prolonged viewing of high-speed stimuli, the stimuli appear to slow down but not to stop. We report psychophysical evidence that the same neural adaptation process likely gives rise to motion fading and to the motion aftereffect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the contrast of the stimulus just before and after illusory cessation of motion does not appear to change. In a recent study (Hsieh & Tse, 2006b), we have shown that when systematically changing the luminance of the stimulus, the perceived speed decrement (and the time to full perceived cessation of motion) does not change, suggesting that motion fading is unlikely to be due to a decrease of luminance contrast or perceived brightness.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Moreover, the contrast of the stimulus just before and after illusory cessation of motion does not appear to change. In a recent study (Hsieh & Tse, 2006b), we have shown that when systematically changing the luminance of the stimulus, the perceived speed decrement (and the time to full perceived cessation of motion) does not change, suggesting that motion fading is unlikely to be due to a decrease of luminance contrast or perceived brightness.…”
mentioning
confidence: 74%
“…A more plausible account is that motion fading arises because of adaptation or fatigue among cortical neurons that encode motion (Hsieh & Tse, 2006b). Such fatiguing or adaptation is presumed to play a role in the well-known motion aftereffect (MAE), in which illusory motion is perceived to occur over a stationary object or image following prolonged exposure to visual motion (Wohlgemuth, 1911).…”
mentioning
confidence: 99%
“…How a form is parsed influences the magnitude of motion signals generated by its perceived shape ( Caplovitz & Tse, 2007b ; Hsieh & Tse, 2007 ), suggesting that a form analysis stage precedes the computation of motion vectors. That the form processing stage and motion processing stage may involve different underlying neural populations is revealed by the finding that motion can adapt to a point that motion perception ceases, in a phenomenon known as “motion fading,” although the form remains statically visible despite it having changed its location in the visual input ( Hsieh & Tse, 2009 ; Kohler, Caplovitz, Hsieh, Sun, & Tse, 2010 ). Moreover, form outputs may interact with translational and rotational motion computations independently ( Porter, Caplovitz, Kohler, Ackerman, & Peter, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their occurrence is crucial for maintaining perception as a perfectly stable image on the retina quickly fades (e.g., Riggs, Ratliff, Cornsweet, & Cornsweet, 1953) (for reviews see Martinez-Conde, Rolfs, 2009). Recent research has shown that perception of peripheral and foveal targets may fade after a period of 200 to 600ms without a microsaccade (Costela, McCamy, Macknik, Otero-Millan, & Martinez-Conde, 2013;Hsieh & Tse, 2009b;Martinez-Conde, Macknik, Troncoso, & Dyar, 2006;McCamy, Macknik, & Martinez-Conde, 2014;Rucci & Desbordes, 2003;Troncoso, Macknik, & Martinez-Conde, 2008) (but see Bonneh et al, 2010). However perception is also compromised around the moment of the movement (Hafed, 2013;Hass & Horwitz, 2011;Maij, Matziridi, Smeets, & Brenner, 2012;Schütz, Braun, & Gegenfurtner, 2009) and it may therefore be adaptive to briefly suppress microsaccades during demanding visual tasks (Bridgeman & Palca, 1980).…”
Section: Introductionmentioning
confidence: 99%